Sentencing and criminal justice - Ashworth, Andrew (Law in context., 2015)
Now in its sixth edition, Sentencing and Criminal Justice has been extensively rewritten to reflect recent legislation, guidelines and judicial decisions. New material includes comparative sentencing research, which looks at models from other countries in comparison with the approach in England and Wales, and an additional chapter focusing on civil preventive orders and other ancillary orders. Written with clarity of expression coupled with critical analysis, this textbook offers an unrivalled combination of expertise, accessibility and coverage. This is the essential text for anyone interested in criminal justice.